The Health Impacts of Relaxing Internal Migration Policies: Quasi-experimental Evidence from China - Fengyu Wu; Julia Shu-Huah Wang; Jing You; Julien Teitler (Global Labor Organization (GLO), 2025)
This study examines the health impacts of a large-scale internal migration reform in China. Using nationally representative data from the China Labor-Force Dynamics Survey (2012-2018) and a unique dataset on city-level policy intensity and adoption timing, we employ a triple-difference approach to estimate the effects of migration policies on migrants' perceived physical and emotional health. We find that more lenient policies significantly improve migrants' health relative to natives. Integration policies yield health benefits approximately 3-4 times greater than selection policies. The most effective policy tools enhancing all health outcomes are integration policies granting migrants access to public services and education and selection policies targeting high-skilled migrants. Health improvements are driven by reduced overtime work, greater social capital, and stronger integration with natives. Analysis of treatment effect heterogeneity indicates that selection policies offer more consistent health benefits across various durations of residence, while integration policies primarily benefit long-term migrants.
Keywords: I18; J61; O15; R23; 330; Health; Migration Policies; Internal Migration; Hukou Reform; China